Kant and mysticism critique as the experience of baring all in reason's light - Palmquist, Stephen (Contemporary studies in idealism, 2019)
Kant and Mysticism interprets Kant's early criticism of Swedenborg's mysticism as the fountainhead of the Critical philosophy. Kantian Critique revolutionizes not only traditional metaphysics, but also our understanding of mysticism: Critical mysticism is a unitive experience that impels us to lay bare all human pretensions to reason's light.